Factors influencing choice of skilled birth attendance at ANC: evidence from the Kenya demographic health survey - Caroline Nyongesa; Xiaoyue Xu; John J. Hall; William M. Macharia; Faith Yego; Brigid Hall (BMC, 2018)
Abstract Background In Kenya, skilled attendance at delivery is well below the international target of 90% and the maternal mortality ratio is high at 362 (CI 254-471) per 100,000 live births despite various interventions. The preventative role of skilled attendance at delivery makes it a benchmark indicator for safe motherhood. Methods Maternal health data from the Service Provision Assessment Survey, a subset of the 2010 Kenya Demographic Health Survey was analyzed. Logistic regression models were employed using likelihood ratio test to explore association between choice of skilled attendance and predictor variables. Results Overall, 94.8% of women are likely to seek skilled attendance at delivery. Cost, education level, number of antenatal visits and sex of provider were strongly associated with client's intention to deliver with a skilled birth attendant at delivery. Women who reported having enough money set aside for delivery were 4.34 (p < 0.002, 95% CI: 1.73; 10.87) times more likely to seek skilled attendance. Those with primary education and above were 6.6 times more likely to seek skilled attendance than those with no formal education (p < 0.001, 95% CI: 3.66; 11.95). Women with four or more antenatal visits were 5.95 (p < 0.018, 95% CI: 1.35; 26.18) times more likely to seek skilled attendance. Compared to men, female providers impacted more on the client's plan (OR = 2.02 (p < 0.014, 95% CI: 1.35; 3.53). Conclusion Interventions aimed at improving skilled attendance at delivery should include promotion of formal education of women and financial preparation for delivery. Whenever circumstances permit, women should be allowed to choose gender of preferred professional attendant at delivery.